Strategi Pengembangan Eksistensi Karyawan di Era Digital Perspektif Teori Core Competence - Yanthy Herawaty Purnama (Journal of Management and Bussines (JOMB), 2023)
This study aims to identify and analyze the most effective strategies for increasing employee presence in the digital age, while examining their relationship within the framework of core competency theory. The methodology for obtaining data requires a rigorous approach in observing and documenting data, which is then carried out by analytical techniques such as data reduction, visualization, and inference to extract significant findings. The results of the study show that in a dynamic digital era landscape, the implementation of employee development strategies is very important for companies to maintain their relevance, adapt to changes, and engage effectively in competition. In conclusion, employee development strategies generate benefits such as gaining competitive advantage, increasing adaptability, encouraging strong team collaboration, encouraging sustainable career growth, and increasing organizational productivity and performance. Keywords: Employee Existence, Digital Era, Core Competency Theory